Foam-molded composition, foam-molded body, electric wire, method for producing foam-molded body, and method for producing electric wire

By using compound B, which has a thermal decomposition temperature of over 300℃ and a solubility parameter of 8-15, as a foaming nucleating agent in fluoropolymers, the problems of uneven bubble distribution and thermal decomposition of fluoropolymers during high-temperature molding were solved, resulting in highly efficient foamed wires with uniform bubble distribution and smooth surfaces.

CN116157462BActive Publication Date: 2026-11-06DAIKIN INDUSTRIES LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202180059681.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-08-03
Filing Date
2021-08-03
Publication Date
2026-11-06
Estimated Expiration
2041-08-03

Smart Images

  • Figure CN116157462B_ABST
    Figure CN116157462B_ABST
Patent Text Reader

Abstract

The present invention aims to provide a foaming composition which can produce a foamed molded body and a foamed wire having a small average bubble diameter, a large foaming ratio, and a small number of sparks, without using a fluorine-based surfactant. A foaming composition characterized by comprising a fluorine resin (A) and a compound (B) having a thermal decomposition temperature of 300°C or higher and a solubility parameter (SP value) of 8 to 15.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to compositions for foam molding, foamed bodies, wires, methods for manufacturing foamed bodies, and methods for manufacturing wires. Background Technology

[0002] To improve electrical properties, it is desirable to reduce the dielectric constant of electrical wires as a coating material. Therefore, using a foamed material is effective in reducing the dielectric constant. Resin-based foams are typically obtained through foaming molding, where gas is present in molten resin and the mixture is then molded.

[0003] To ensure uniform shape and properties of the resulting foam, the air bubbles in the foam are preferably fine and evenly distributed. To achieve this fineness and uniform distribution of air bubbles, a method exists where a foaming nucleating agent is present in the resin to serve as the starting point for bubble generation during foaming.

[0004] Sulfonates are used as foaming nucleating agents added to resins such as fluoropolymers. Methods for obtaining foams by mixing sulfonates are disclosed below.

[0005] Patent document 1 describes a foaming method for a fluoropolymer resin that can be melt-processed in the presence of a boron nitride nucleating agent and (a) at least one inorganic salt containing a polyatomic anion, or (b) at least one sulfonic acid or phosphonic acid or a salt thereof, or (c) a combination of (a) and (b).

[0006] Patent document 2 discloses a composition characterized by comprising a fluoropolymer (A) and a compound (B), wherein the compound (B) has the following formula (1):

[0007] F(CF2) n SO3H (1)

[0008] (In the formula, n is 4 or 5.) Or the following formula (2):

[0009] F(CF2) n CH2CH2SO3H (2)

[0010] (where n is 4 or 5.) sulfonic acids, or their salts.

[0011] Patent Document 3 discloses a foaming nucleating agent containing at least one compound selected from the group consisting of phosphate ester complex compounds (a-1) and phosphate ester compounds (a-2), with an average particle size of 0.01 μm to 300 μm; and discloses a foam composition containing the above-mentioned foaming nucleating agent and a resin component (B), wherein the resin component (B) is at least one component selected from the group consisting of elastomers (b-1) and thermoplastic resins (b-2).

[0012] Patent document 4 discloses a composition for wallpaper, which is made by adding a foaming agent and an aromatic cyclic phosphate salt with a specific structure as a foaming nucleating agent to a thermoplastic elastomer.

[0013] Existing technical documents

[0014] Patent documents

[0015] Patent Document 1: Japanese Patent Application Publication No. 10-45931

[0016] Patent Document 2: Japanese Patent Application Publication No. 2014-224229

[0017] Patent Document 3: Japanese Patent Application Publication No. 2013-147566

[0018] Patent Document 4: Japanese Patent Application Publication No. 11-130892 Summary of the Invention

[0019] The problem that the invention aims to solve

[0020] The purpose of this invention is to provide a composition for foaming molding that can manufacture foamed molded bodies and foamed wires with small average bubble diameter, high foaming rate and low spark generation without using fluorinated surfactants.

[0021] Methods for solving problems

[0022] The present invention relates to a composition for foaming molding, characterized in that it comprises a fluoropolymer (A) and a compound (B) having a thermal decomposition temperature of 300°C or higher and a solubility parameter (SP value) of 8 to 15.

[0023] The above-mentioned compound (B) is preferably a compound containing at least one of the following groups: aromatic ring, phosphate group and amide group.

[0024] The above-mentioned compound (B) is preferably a compound containing one or more C6-14 aromatic rings or a salt thereof.

[0025] The compound (B) is preferably at least one compound selected from the group consisting of phosphate esters and their salts, phosphate ester complexes, and compounds containing two or more amide groups.

[0026] The salt of the above compound (B) is preferably an alkali metal or an alkaline earth metal.

[0027] The above-mentioned compound (B) is preferably at least one of the compounds shown in the following formulas (1), (2), (3) and (4).

[0028]

Chemistry 1

[0029]

[0030]

Chemistry 2

[0031]

[0032]

Transformation 3

[0033]

[0034]

Chemistry 4

[0035]

[0036] (In the formula, R1, R2, R3, R4, R...) 21 R 22 R 23 R 24 R 31 R 32 R 33 R 34 R 41 R 42 Ar represents hydrogen atoms, alkyl or cycloalkyl groups having 1 to 8 carbon atoms, or aryl, alkylaryl, or aralkyl groups having 6 to 12 carbon atoms. 41 R5 and R6 represent hydrogen atoms or methyl groups, n represents an integer of 1 or 2, m represents an integer from 0 to 2, and X represents a metal with a valence of m+n.

[0037] R1, R2, and R in equations (1), (2), and (3) above 21 R 22 R 31 and R 33 Preferably, it is an alkyl group having 1 to 8 carbon atoms.

[0038] In the above formulas (1), (2), and (3), X is preferably at least one of sodium, potassium, rubidium, calcium, and barium.

[0039] The above compound (B) is preferably an aromatic cyclic phosphate salt as shown in the above formula (1).

[0040] The compound (B) is preferably sodium 2,2'-methylenebis(4,6-di-tert-butylphenyl) phosphate.

[0041] The fluororesin (A) mentioned above is preferably a melt-processable fluororesin.

[0042] The fluororesin (A) is preferably selected from at least one group consisting of tetrafluoroethylene / hexafluoropropylene copolymer, tetrafluoroethylene / perfluoro(alkyl vinyl ether) copolymer, and tetrafluoroethylene / ethylene copolymer.

[0043] The fluororesin (A) mentioned above is preferably a fluorinated fluororesin.

[0044] The above-mentioned foaming molding composition preferably does not contain fluorine-based low molecular weight compounds.

[0045] The present invention also relates to a foamed molded article, characterized in that it is obtained from the above-mentioned foaming molding composition.

[0046] The foamed molded articles described above preferably do not contain fluorine-based low molecular weight compounds.

[0047] The present invention also relates to an electrical wire, characterized in that it comprises a core wire and a coating material obtained from the above-described foaming molding composition covering the core wire.

[0048] The aforementioned wires preferably do not contain fluorine-based low-molecular-weight compounds.

[0049] The present invention also relates to a foamed wire having a core wire and a fluoropolymer layer or fluoropolymer composition layer covering the core wire, wherein the fluoropolymer layer or fluoropolymer composition layer has air bubbles.

[0050] The foamed wire is characterized in that, when viewed in a cross-section parallel to the length direction, the average aspect ratio of the bubbles is less than 1.9.

[0051] The present invention also relates to a foamed wire having a core wire and a fluoropolymer layer or fluoropolymer composition layer covering the core wire, wherein the fluoropolymer layer or fluoropolymer composition layer has air bubbles.

[0052] The foamed wire is characterized in that, in a cross-sectional view parallel to the length direction, the proportion of bubbles with an aspect ratio of 3 or higher is less than 13% of the total number of bubbles measured in the cross-sectional view parallel to the length direction.

[0053] The present invention also relates to a foamed wire having a core wire and a fluoropolymer layer or fluoropolymer composition layer covering the core wire, wherein the fluoropolymer layer or fluoropolymer composition layer has air bubbles.

[0054] The foamed wire is characterized in that, when viewed in a cross-section parallel to the length direction, the standard deviation of the aspect ratio of the bubble is less than 1.3.

[0055] The present invention also relates to a foamed wire having a core wire and a fluoropolymer layer or fluoropolymer composition layer covering the core wire, wherein the fluoropolymer layer or fluoropolymer composition layer has air bubbles.

[0056] The foamed wire is characterized by a foaming rate of over 35% and a surface roughness of less than 9.0 μm.

[0057] Preferably, the foamed wire described above has an average bubble diameter of less than 40 μm when viewed in a cross-section perpendicular to the length direction.

[0058] The present invention also relates to a method for manufacturing a foamed molded article, characterized in that it includes a step of foaming the above-mentioned foaming molding composition.

[0059] The present invention also relates to a method for manufacturing an electrical wire, characterized in that it includes a step of coating the above-mentioned foaming molding composition onto a core wire to obtain an electrical wire.

[0060] Invention Effects

[0061] The foaming molding composition of the present invention, having the above-described structure, can produce foamed molded bodies and foamed wires with high foaming rate, small average bubble diameter, low spark generation, small outer diameter / capacitance unevenness, and smooth surface. Attached Figure Description

[0062] Figure 1 This is a cross-sectional photograph of the wire obtained in Example 1.

[0063] Figure 2 This is a cross-sectional photograph of the wire obtained in Example 2.

[0064] Figure 3 This is a cross-sectional photograph of the wire obtained in Example 3.

[0065] Figure 4 This is a cross-sectional photograph of the wire obtained in Example 4.

[0066] Figure 5 This is a photograph of the cross-section of the wire obtained in Comparative Example 2.

[0067] Figure 6 This is a photograph of the cross-section of the wire obtained in Comparative Example 3.

[0068] Figure 7 This is a photograph of the cross-section of the wire obtained in Comparative Example 4.

[0069] Figure 8 This is a photograph of the cross-section of the wire obtained in Comparative Example 5.

[0070] Figure 9 This is a photograph of the cross-section of the wire obtained in Comparative Example 6.

[0071] Figure 10 This is a photograph of the cross-section of the wire obtained in Comparative Example 7.

[0072] Figure 11 This is a photograph of the cross-section of the wire obtained in Comparative Example 8.

[0073] Figure 12This is a photograph of the surface of the wire obtained in Example 1.

[0074] Figure 13 This is a photograph of the surface of the wire obtained in Example 2.

[0075] Figure 14 This is a photograph of the surface of the wire obtained in Example 3.

[0076] Figure 15 This is a photograph of the surface of the wire obtained in Example 4.

[0077] Figure 16 This is a photograph of the surface of the wire obtained in Comparative Example 2.

[0078] Figure 17 This is a photograph of the surface of the wire obtained in Comparative Example 3.

[0079] Figure 18 This is a photograph of the surface of the wire obtained in Comparative Example 4.

[0080] Figure 19 This is a photograph of the surface of the wire obtained in Comparative Example 5.

[0081] Figure 20 This is a photograph of the surface of the wire obtained in Comparative Example 6.

[0082] Figure 21 This is a photograph of the surface of the wire obtained in Comparative Example 7.

[0083] Figure 22 This is a photograph of the surface of the wire obtained in Comparative Example 8.

[0084] Figure 23 This is a cross-sectional photograph of the wire obtained in Example 5.

[0085] Figure 24 This is a photograph of the surface of the wire obtained in Example 5.

[0086] Figure 25 This is a cross-sectional photograph of the wire obtained in Example 6.

[0087] Figure 26 This is a photograph of the surface of the wire obtained in Example 6. Detailed Implementation

[0088] The present invention is disclosed by the following discovery: good foaming can be obtained by using a specific compound (B) in a foaming resin with a fluoropolymer as the base resin.

[0089] The compound (B) has a thermal decomposition temperature above 300°C and a solubility parameter (SP value) of 8–15. Most existing foaming nucleating agents have relatively low thermal decomposition temperatures and melting points. While this is not a problem when the resin molding temperature is low, in molding compositions containing resins with high melting points, the following issues arise: thermal decomposition or melting occurs during molding, rendering it ineffective as a foaming nucleating agent. In particular, when using fluoropolymers, which are high-melting-point resins, adverse effects such as discoloration, generation of decomposition gases, large bubble size, deterioration of surface condition, and deterioration of electrical properties occur, making it difficult to balance the physical properties of fluoropolymers with the characteristics of foamed molded articles.

[0090] The present invention has discovered that by using compound (B), the composition containing fluororesin (A) exhibits good foaming properties, and furthermore, it exhibits good properties even when molded at high temperatures, thereby achieving the aforementioned effects.

[0091] The present invention will now be described in detail.

[0092] Fluoropolymers (A) are not particularly limited as long as they can be melt-processed. Examples include tetrafluoroethylene (TFE) / hexafluoropropylene (HFP) copolymers, TFE / perfluoro(alkyl vinyl ether) (PAVE) copolymers, TFE / ethylene copolymers [ETFE], trifluorochloroethylene (CTFE) / ethylene copolymers [ECTFE], polyvinylidene fluoride [PVdF], polytrifluorochloroethylene [PCTFE], TFE / vinylidene fluoride (VdF) copolymers [VT], polyvinyl fluoride [PVF], TFE / VdF / CTFE copolymers [VTC], TFE / ethylene / HFP copolymers, and TFE / HFP / VdF copolymers.

[0093] Examples of PAVEs mentioned above include perfluoro(methyl vinyl ether) [PMVE], perfluoro(ethyl vinyl ether) [PEVE], and perfluoro(propyl vinyl ether) [PPVE]. PPVE is preferred. One or more of these can be used.

[0094] Fluoropolymers can contain polymerization units based on other monomers in amounts that do not impair the inherent properties of each fluoropolymer. These other monomers can be suitably selected from, for example, TFE, HFP, ethylene, propylene, perfluoro(alkyl vinyl ether), perfluoroalkyl ethylene, hydrofluoroolefin, fluoroalkyl ethylene, and perfluoro(alkyl allyl ether). As the perfluoroalkyl group constituting these other monomers, a perfluoroalkyl group having 1 to 10 carbon atoms is preferred.

[0095] Due to their excellent heat resistance, fluoropolymers are preferably TFE / HFP copolymers, TFE / PAVE copolymers, or TFE / ethylene copolymers, with TFE / HFP copolymers or TFE / PAVE copolymers being more preferred. Two or more of the above-mentioned fluoropolymers may also be used in combination. Furthermore, due to their superior electrical properties, perfluorinated resins are also preferred.

[0096] In the TFE / HFP copolymer, the TFE / HFP ratio is preferably 80-97 / 3-20 by mass, and more preferably 84-92 / 8-16.

[0097] TFE / HFP copolymers can be binary copolymers composed of TFE and HFP, or terpolymers including comonomers capable of copolymerizing with TFE and HFP (e.g., TFE / HFP / PAVE copolymers).

[0098] TFE / HFP copolymers are also preferably TFE / HFP / PAVE copolymers containing PAVE-based polymerization units.

[0099] In the TFE / HFP / PAVE copolymer, the TFE / HFP / PAVE ratio is preferably 70-97 / 3-20 / 0.1-10 by mass, and more preferably 81-92 / 5-16 / 0.3-5.

[0100] In the TFE / PAVE copolymer, the TFE / PAVE ratio is preferably 90-99 / 1-10 by mass, and more preferably 92-97 / 3-8.

[0101] In TFE / ethylene copolymers, the TFE / ethylene molar ratio is preferably 20–80 / 20–80, more preferably 40–65 / 35–60. Additionally, TFE / ethylene copolymers may also contain other monomer components.

[0102] That is, the TFE / ethylene copolymer can be a binary copolymer composed of TFE and ethylene, and further, it can be a terpolymer including comonomers capable of copolymerizing with TFE and ethylene (e.g., TFE / ethylene / HFP copolymer).

[0103] TFE / ethylene copolymers are also preferably TFE / ethylene / HFP copolymers containing HFP-based polymerization units. In the TFE / ethylene / HFP copolymer, the molar ratio of TFE / ethylene / HFP is preferably 40-65 / 30-60 / 0.5-20, more preferably 40-65 / 30-60 / 0.5-10.

[0104] The melt flow rate (MFR) of the fluoropolymer is preferably 0.1 g / 10 min to 500 g / 10 min. More preferably, it is 4 g / 10 min to 100 g / 10 min, and even more preferably, it is 10 g / 10 min to 80 g / 10 min. Since it can suppress the generation of sparks and increase the foaming rate, it is even more preferably 34 g / 10 min to 50 g / 10 min, and particularly preferably 35 g / 10 min to 40 g / 10 min.

[0105] The above MFR is a value determined according to ASTM D-1238, using a die with a diameter of 2.1 mm and a length of 8 mm, under a load of 5 kg and a temperature of 372 °C.

[0106] Fluoropolymers can be synthesized by polymerizing monomer components using common polymerization methods, such as emulsion polymerization, suspension polymerization, solution polymerization, bulk polymerization, and gas-phase polymerization. In these polymerization reactions, chain transfer agents such as methanol are sometimes used. Fluoropolymers can also be manufactured by polymerization and separation without the use of reagents containing metal ions.

[0107] Fluoropolymers may have terminal groups such as -CF3 and -CF2H at at least one site in the polymer backbone and polymer side chains, without particular limitation, but fluorinated fluoropolymers are preferred. Unfluorinated fluoropolymers sometimes have terminal groups such as -COOH, -CH2OH, -COF, and -CONH2 that are unstable in thermal and electrical properties (hereinafter, such terminal groups are also referred to as "unstable terminal groups"). These unstable terminal groups can be reduced by the above-mentioned fluorination treatment. Fluoropolymers preferably have few or no unstable terminal groups, and the total number of the above four unstable terminal groups and the -CF2H terminal group is relative to 1 × 10 6 The number of carbon atoms is more preferably 50 or less. If it exceeds 50, poor molding may occur. The number of unstable terminal groups is more preferably 20 or less, and even more preferably 10 or less. In this specification, the number of unstable terminal groups is a value obtained by infrared absorption spectroscopy. Alternatively, the unstable terminal groups and -CF2H terminal groups may be absent, and all terminal groups may be -CF3.

[0108] The above-mentioned fluorination treatment can be carried out by contacting an unfluorinated fluororesin with a fluorinated compound.

[0109] There are no particular limitations on the fluorinated compounds mentioned above; any fluorine radical source that generates fluorine radicals under fluorination conditions can be cited. Examples of such fluorine radical sources include F2 gas, CoF3, AgF2, UF6, OF2, N2F2, CF3OF, and fluorinated halogens (e.g., IF5, ClF3).

[0110] The aforementioned fluorine radical source, such as F2 gas, can be 100% F2 gas, but from a safety perspective, it is preferable to dilute it to 5% to 50% by mass, more preferably 15% to 30% by mass, by mixing it with an inert gas. Examples of inert gases include nitrogen, helium, and argon; from an economic perspective, nitrogen is preferred.

[0111] The conditions for the above fluorination treatment are not particularly limited. The molten fluororesin can be brought into contact with the fluorinated compound. Generally, the treatment can be carried out at a temperature below the melting point of the fluororesin, preferably 20°C to 220°C, and more preferably 100°C to 200°C. The above fluorination treatment is usually carried out for 1 hour to 30 hours, preferably 5 hours to 20 hours.

[0112] The above-mentioned fluorination treatment preferably involves contacting the unfluorinated fluororesin with fluorine gas (F2 gas).

[0113] There are no particular limitations on the fluoropolymer (A), but since it can produce foamed molded articles with excellent heat resistance and a wide continuous use temperature range, it is preferable that the melting point is 200°C or higher, the molding temperature is 250°C or higher, and the thermal decomposition temperature is 300°C or higher. More preferably, the melting point is 250°C or higher, and more preferably 300°C or lower. The molding temperature is more preferably 300°C or higher, and more preferably 450°C or lower. The thermal decomposition temperature is more preferably 350°C or higher, and even more preferably 400°C or higher. The upper limit for the melting point, molding temperature, and thermal decomposition temperature is 600°C or lower.

[0114] In this specification, the melting point is the temperature measured using a differential scanning calorimeter (DSC). The molding temperature is the generally recommended suitable molding temperature, the temperature at which the resin exhibits fluidity without coloration or other resin degradation. The thermal decomposition temperature is the 1% weight loss temperature obtained by TG (thermal weight change measurement) when heated in air at 10°C / min. This does not include the weight loss due to the volatilization of water or water of crystallization observed between 100°C and 200°C. Fluidity is defined as an MFR of 0.0001 or higher at this temperature.

[0115] To reduce signal loss in communication cables, the dielectric constant of the aforementioned fluororesin (A) is preferably 3.0 or less, more preferably 2.6 or less, and most preferably 2.1 or less. As a lower limit, it is 1.0 or more. Similarly, the dielectric loss tangent is preferably 0.01 or less, more preferably 0.001 or less, and most preferably 0.0004 or less. As a lower limit, it is 0.0001 or more. The dielectric constant and dielectric loss tangent are measured using the cavity resonator method at a frequency of 6 GHz.

[0116] The content of the aforementioned fluoropolymer (A) relative to 100 parts by weight of the foaming molding composition is preferably 50 parts by weight or more, more preferably 80 parts by weight or more. Further preferably, it is 90 parts by weight or more, even more preferably 95 parts by weight or more, and particularly preferably 98 parts by weight or more. As an upper limit, it is 99.999 parts by weight or less, more preferably 99.99 parts by weight or less.

[0117] In this invention, the compound (B) that functions as a foaming nucleating agent is a compound with a thermal decomposition temperature of 300°C or higher and a solubility parameter (SP value) of 8 to 15.

[0118] In this invention, since a foamed molded body with excellent heat resistance and a wide continuous operating temperature range can be obtained, the thermal decomposition temperature of compound (B) must be 300°C or higher. More preferably, the thermal decomposition temperature is 350°C or higher, and even more preferably 400°C or higher. As an upper limit, it is preferably 600°C or lower.

[0119] The thermal decomposition temperature can be determined in the same manner as that of the fluoropolymer (A) described above.

[0120] To effectively achieve the effects of the present invention, it is preferable that compound (B) does not melt at the molding temperature. Therefore, the melting point of compound (B) is preferably 200°C or higher, more preferably 300°C or higher, further preferably 350°C or higher, and most preferably 400°C or higher. The melting point of compound (B) is the temperature that can be confirmed by the TGA peak during TG measurement; for example, if the peak cannot be confirmed below 400°C, it is considered to be 400°C or higher.

[0121] It is possible to confirm whether the compound melts at the peak temperature by means of observation using a heated microscope or an electric furnace.

[0122] Furthermore, the solubility parameter (SP value) of the aforementioned compound (B) is 8 to 15. By keeping the SP value within this range, the additive particles can be uniformly dispersed, resulting in uniform and fine foaming. This leads to the following effects: suppressing the formation of large particles due to particle re-aggregation during foaming and molding, reducing the unevenness of the wire surface caused by large particles, and achieving a smooth surface.

[0123] The SP value is preferably 9 or more, more preferably 10 or more. Furthermore, it is preferably 14 or less, more preferably 13 or less, and even more preferably 12 or less.

[0124] The above SP values ​​can be obtained by Fedors' formula (Polym.Eng.Sci.,14[2],147(1974)).

[0125] The compound (B) described above is preferably a compound containing at least one of the following partial structures: an aromatic ring, a phosphate group, and an amide group. For example, when the compound (B) described above contains an aromatic ring, it is preferably a compound containing one or more C6-14 aromatic rings or a salt thereof.

[0126] When the above-mentioned compound (B) contains an amide group, it is preferred to be a compound having two or more amide groups. There are no particular limitations on such compounds, but for example, compounds represented by the following formula (4) are preferred.

[0127]

Transformation 5

[0128]

[0129] (where R is in the formula) 41 R 42 Ar represents hydrogen atoms, alkyl or cycloalkyl groups having 1 to 8 carbon atoms, or aryl, alkylaryl, or aralkyl groups having 6 to 12 carbon atoms. 41 (Indicates aryl.)

[0130] More specifically, examples include N,N'-dicyclohexyl-2,6-naphthalenedicarboxamide (trade name: NJSTAR NU-100, Shin Nippon Rikka Co., Ltd.).

[0131] When the above-mentioned compound (B) contains a phosphate ester group, it is preferably at least one compound selected from the group consisting of phosphate esters and their salts, and phosphate ester complexes. Phosphate ester compounds that can be used as the above-mentioned compound (B) are typically phosphate esters, phosphites, acidic phosphate esters, acidic phosphites, or their salts of ammonia, amines, melamine, alkali metals, or alkaline earth metals, and their specific structures are not particularly limited.

[0132] Specific examples include: triphenyl phosphate, trilauryl phosphate, tristearyl phosphate, trioleyl phosphate, xylene diphenyl phosphate, ethyl diphenyl phosphate, isopropyl diphenyl phosphate, n-butyl diphenyl phosphate, 2-ethylhexyl diphenyl phosphate, isodeyl diphenyl phosphate, hexadecyl diphenyl phosphate, stearyl diphenyl phosphate, oleyl diphenyl phosphate, butyl xylene phosphate, octyl xylene phosphate, lauryl xylene phosphate, and dibutyl... pyrophosphate, monophenyl phosphate, diphenyl phosphate, monotolyl phosphate, xylyl phosphate, monoxylyl phosphate, 2-acryloyloxyethyl phosphate, 2-methacryloyloxyethyl phosphate, diphenyl(2-acryloyloxyethyl) phosphate, diphenyl(2-methacryloyloxyethyl) phosphate, trinaphthyl phosphate, trinonylphenyl phosphate, tris(2,6-dimethylphenyl) phosphate, tetraphenylresorcinol diphosphate Esters, tetraphenylhydroquinone diphosphate, tetraphenylbisphenol A diphosphate, tetra(2,6-dimethylphenyl)resorcinol diphosphate, tetra(2,6-dimethylphenyl)bisphenol A diphosphate, tetra(2,6-dimethylphenyl)biphenyl diphosphate, tetraphenylethylene glycol diphosphate, bis(2,6-dimethylphenyl)pentaerythritol diphosphate, bis(xylyl)carboxylic acid phosphate, and other acidic phosphates, or acidic phosphites, dimethyl phosphate ammonium salts, diethyl phosphate ammonium salts, ethyl phosphates, etc. Acidic phosphates such as ester·ammonium salt, di-n-butyl phosphate·ammonium salt, dibutoxyethyl phosphate·triethanolamine salt, dioctyl phosphate·morpholine salt, mono-n-butyl phosphate·sodium salt, diphenyl phosphate·ammonium salt, diphenyl phosphate·melamine salt, diphenyl phosphate·piperazine salt, phenyl phosphate·ammonium salt, xylyl phosphate·ethylenediamine salt, tolyl phosphate·sodium salt, bis(xylyl) phosphate·melamine salt, etc., or acidic phosphites such as ammonia, amine, melamine, alkali metal or alkaline earth metal salts.

[0133] More specifically, examples include salts of phosphate esters such as sodium bis(4-tert-butylphenyl) phosphate and sodium 2,2'-methylenebis(4,6-di-tert-butylphenyl) phosphate, sodium salt of (2-hydroxy-2-oxo-4,6,10,12-tetra-tert-butyl-1,3,2-dibenzo[d,g]perhydrodioxophosphorus octacyclic salt), barium salt of bisphenol phosphate diester, sodium salt of binatidine phosphate diester, and sodium bis(4-nitrophenyl) phosphate. Furthermore, esters can be monoesters, diesters, triesters, or tetraesters and above. They can be used alone or in combination.

[0134] Among them, aromatic phosphates are preferred, salts of aromatic phosphates are more preferred, and salts of aromatic phosphates having a cyclic structure are even more preferred. Salts of cyclic phosphates having a biphenyl structure, a naphthalene structure, or a diphenylmethyl structure are more preferred, wherein these benzene rings or naphthalene rings may have an alkyl or cycloalkyl group having 1 to 8 carbon atoms, or an aryl, alkylaryl, or aralkyl group having 6 to 12 carbon atoms.

[0135] As an aromatic phosphate salt having the above-mentioned cyclic structure, it is preferably at least one of the aromatic cyclic phosphate salts shown in the following formulas (1), (2) and (3).

[0136]

Transformation 6

[0137]

[0138]

Transformation 7

[0139]

[0140]

Transformation 8

[0141]

[0142] In the formula, R1, R2, R3, R4, R 21 R 22 R 23 R 24 R 31 R 32 R 33 R 34 R5 and R6 represent hydrogen atoms, alkyl or cycloalkyl groups with 1 to 8 carbon atoms, or aryl, alkylaryl or aralkyl groups with 6 to 12 carbon atoms. R5 and R6 represent hydrogen atoms or methyl groups. n represents an integer of 1 or 2. m represents an integer of 0 to 2. X represents a metal with a valence of m+n.

[0143] As R1, R2, R3, R4, R 21 R 22 R 23 R 24 R 31 R 32 R 33 R 34 Examples of alkyl groups include methyl, ethyl, propyl, isopropyl, butyl, isobutyl, sec-butyl, tert-butyl, pentyl, isopentyl, sec-pentyl, tert-pentyl, hexyl, isohexyl, heptyl, octyl, isooctyl, 2-ethylhexyl, and tert-octyl. Examples of cycloalkyl groups include cyclopentyl, cyclohexyl, and cycloheptyl. Alkyl groups with 1 to 4 carbon atoms and tert-butyl are preferred.

[0144] As R1, R2, R3, R4, R21 R 22 R 23 R 24 R 31 R 32 R 33 R 34 Examples of aryl groups include phenyl, naphthyl, and biphenyl. Examples of alkylaryl groups include 4-methylphenyl, 4-tert-butylphenyl, and nonylphenyl. Examples of aralkyl groups include benzyl, phenethyl, and isopropylphenyl.

[0145] Examples of metals represented by X include alkali metals such as lithium, sodium, potassium, and rubidium; alkaline earth metals such as magnesium, calcium, and barium; aluminum; zinc; and titanium. Among these, at least one of sodium, potassium, rubidium, calcium, and barium is preferred, and sodium or barium is more preferred.

[0146] The compound (B) is preferably an aromatic cyclic phosphate salt as shown in formula (1) above, and more specifically, is most preferably sodium 2,2'-methylenebis(4,6-di-tert-butylphenyl) phosphate as shown in formula (5) below.

[0147]

Chemistry 9

[0148]

[0149] The phosphate ester complex that can be used as compound (B) above is a complex composed of a metal and an organic compound having a phosphate ester, and its specific structure is not particularly limited. Examples of organic compounds constituting this complex include, for example, bis(4,4',6,6'-tetratert-butyl-2,2'-methylenediphenyl phosphate, 2,2'-methylene-bis(4,6-ditert-butylphenyl) phosphate, 2,2'-methylene-bis(4,6-dimethylphenyl) phosphate, 2,2'-methylene-bis(4,6-dimethylphenyl) phosphate, 2,2'-methylene-bis(4,6-dimethylphenyl) phosphate, 2,2'-methylene-bis(4,6-diethylphenyl) phosphate, 2,2'-methylene-bis(4-methyl-6-tert-butylphenyl) phosphate, and 2,2'-methylene-bis(4-ethyl-6-tert-butylphenyl) phosphate. Ester, 2,2'-Ethylene-bis(4,6-di-tert-butylphenyl) phosphate, 2,2'-Ethylene-bis(4-isopropyl-6-tert-butylphenyl) phosphate, 2,2'-Ethylene-bis(4-m-butyl-6-tert-butylphenyl) phosphate, 2,2'-Butylene-bis(4,6-dimethylphenyl) phosphate, 2,2'-Butylene-bis(4,6-di-tert-butylphenyl) phosphate, 2,2'-tert-octylmethylene-bis(4,6-dimethylphenyl) phosphate, 2,2'-tert-octylmethylene-bis(4,6-di-tert-butylphenyl) phosphate, bis[2,2'-thiobis(4-ethyl [-6-tert-butylphenyl) phosphate], bis[2,2'-thiobis(4,6-di-tert-butylphenyl) phosphate], bis[2,2'-thiobis-(4-tert-octylphenyl) phosphate], bis[2,2'-methylene-bis(4,6-di-tert-butylphenyl) phosphate], bis[2,2'-ethylidene-bis(4,6-di-tert-butylphenyl) phosphate], bis[(4,4'-dimethyl-6,6'-di-tert-butyl-2,2'-biphenyl) phosphate], (4,4'-dimethyl-5,6'-di-tert-butyl-2,2'-biphenyl) phosphate, tris[2,2'-methylene-bis(4,6-di-tert-butylphenyl) phosphate] [Butylphenyl) phosphate], Tris[2,2'-Ethylene-bis(4,6-di-tert-butylphenyl) phosphate], Phenyl bis(dodecyl) phosphate, Phenyl ethyl hydrogen phosphate, Phenyl bis(3,5,5-trimethylhexyl) phosphate, Ethyl diphenyl phosphate, 2-Ethylhexyl di(tolyl) phosphate, Diphenyl hydrogen phosphate, Methylene diphenyl phosphate, Bis(2-ethylhexyl)-p-tolyl phosphate, Trimethylbenzene phosphate, Bis(2-ethylhexyl)phenyl phosphate, Di(nonyl)phenyl phosphate, Phenylmethyl hydrogen phosphate, Bis(dodecyl)-p-tolyl phosphate, p-Tolylbis(2,5,5-)5-Trimethylhexyl) phosphate, 2-ethylhexyl diphenyl phosphate, tris(butoxyethyl) phosphate, trioctyl phosphate, trimethylbenzyl phosphate, tolyl diphenyl phosphate, diethylchlorophosphate, diphenylchlorophosphate, diethylbromophosphate, diphenylbromophosphate, dimethylchlorophosphate, phenylchlorophosphate, trimethyl phosphate, triethyl phosphate, tri-n-butyl phosphate, tridecyl phosphate, triphenyl phosphate, isopropyltriphenyl phosphate, isodecyl diphenyl phosphate, methylene diphenyl phosphate, etc.

[0150] In addition, examples of metals constituting phosphate ester complexes include aluminum, sodium, lithium, calcium, magnesium, and barium. They can be used alone or in combination of two or more. Among these, aromatic phosphates are preferred, cyclic aromatic phosphates are more preferred, and sodium complexes of aromatic cyclic phosphates are most preferred.

[0151] Among the compounds (B) mentioned above, compounds with a melting point of 300°C or higher can be specifically exemplified by sodium 2,2'-methylenebis(4,6-di-tert-butylphenyl) phosphate.

[0152] The content of the above-mentioned compound (B) relative to the above-mentioned fluororesin (A) is preferably 20 parts by mass or less, more preferably 10 parts by mass or less. It is further preferably 5 parts by mass or less, even more preferably 2 parts by mass or less, and particularly preferably 1.5 parts by mass or less.

[0153] The content of the above-mentioned compound (B) is preferably 0.001 parts by mass or more relative to the above-mentioned fluororesin (A). More preferably, it is 0.01 parts by mass or more.

[0154] If the content of compound (B) is too low, it will be difficult to obtain fine bubbles in the resulting coating material; if the content of compound (B) is too high, it may generate a large number of sparks.

[0155] The foaming composition of the present invention may further contain boron nitride without impairing the effects of the present invention.

[0156] The average particle size of boron nitride is preferably 8.0 μm or greater. Previously, the average particle size of boron nitride tended to decrease, and the use of boron nitride with a larger average particle size has not been specifically studied.

[0157] The foaming molding composition of the present invention, by containing boron nitride having an average particle size within the above-mentioned specific range, can form foamed wires with a coating material having a smaller average bubble size and a larger foaming rate.

[0158] The average particle size of boron nitride is more preferably 9.0 μm or more, further preferably 10.0 μm or more, even more preferably 10.5 μm or more, particularly preferably 11.0 μm or more, particularly more preferably 12.0 μm or more, and most preferably 13.0 μm or more.

[0159] Furthermore, if the average particle size of boron nitride is too large, the average bubble size may increase, or a large number of sparks may be generated. The average particle size of boron nitride is preferably 25 μm or less, more preferably 20 μm or less.

[0160] By making the average particle size of boron nitride within the above range, it is possible to form a coating material with fine and uniform bubbles.

[0161] The average particle size of boron nitride was determined using a laser diffraction / scattering particle size distribution analyzer. When using a wet method, the appropriate medium can be selected, such as methanol.

[0162] The preferred boron nitride particle size distribution is (D84-D16) / D50, which is below 1.2.

[0163] D84, D50, and D16 represent the particle sizes (μm) at the 84% percentile, 50% percentile, and 16% percentile points of the cumulative curve when the total volume of the boron nitride powder aggregate is set to 100%. It should be noted that the particle size distribution is accumulated from the smallest particle size side. The total volume of the aforementioned powder aggregate is obtained by preparing a sample in which boron nitride powder is dispersed in a medium such as methanol and using a laser diffraction / scattering particle size distribution analyzer (e.g., a Microtrac MT3300 manufactured by Nikkiso Corporation).

[0164] By distributing the boron nitride particle size within the range described above, a coating material with fine and uniform bubbles can be formed, and the generation of sparks can be further suppressed.

[0165] The particle size distribution described above is more preferably 1.1 or less, and even more preferably 1.0 or less. The lower limit of the particle size distribution is not particularly limited, and for example it can be 0.1.

[0166] The cumulative curves for the particle size distribution (volume particle size distribution) described above were obtained using a laser diffraction / scattering particle size distribution analyzer (e.g., the Microtrac MT3300 manufactured by Nikkiso Corporation). When using a wet method, the medium can be appropriately selected, for example, methanol.

[0167] Boron nitride is preferably pulverized boron nitride. When boron nitride is pulverized boron nitride, it can further suppress the generation of sparks.

[0168] The above-mentioned pulverization can be carried out using methods and conditions that allow the average particle size and particle size distribution of boron nitride to fall within the aforementioned range. For example, the type and conditions of the pulverizer can be appropriately selected. Examples of such pulverizers include jet mills, hammer mills, ball mills, and pin mills.

[0169] Boron nitride can be adjusted to the above-mentioned range of average particle size or particle size distribution through grading.

[0170] While there are no particular limitations on the composition of the present invention, the content of boron nitride is preferably, for example, 0.1% to 10% by mass, more preferably 0.1% to 2.0% by mass, further preferably 0.1% to 1.5% by mass, and even more preferably 0.1% to 1.0% by mass. If the content of boron nitride is too low, it may be difficult to obtain fine bubbles in the coating material of the resulting foamed wire; if the content of boron nitride is too high, the manufacturing cost may increase.

[0171] The foaming composition of the present invention may further contain inorganic salts containing polyatomic anions without impairing the effects of the present invention.

[0172] As an example of the aforementioned inorganic salt containing polyatomic anions, the inorganic salt containing polyatomic anions disclosed in U.S. Patent No. 4,764,538 can be cited.

[0173] The foaming composition of the present invention may further contain sulfonic acid, phosphonic acid or their salts, zeolite, etc., without impairing the effects of the present invention. Additionally, organic foaming nucleating agents such as ADCA (azodicarbonamide), DPT (N,N'-dinitropentamethylenetetramine), and OBSH (4,4'-oxobis(benzenesulfonylhydrazine)) can be used in combination.

[0174] In addition to fluoropolymer (A) and compound (B), the foaming composition of the present invention may contain conventionally known filler materials to a extent that does not impair the effects of the present invention.

[0175] Examples of filler materials mentioned above include graphite, carbon fiber, coke, silicon dioxide, zinc oxide, magnesium oxide, magnesium sulfate, tin oxide, antimony oxide, calcium carbonate, magnesium carbonate, magnesium hydroxide, glass, talc, mica, aluminum nitride, calcium phosphate, sericite, diatomaceous earth, silicon nitride, fine silica, fumed silica, alumina, zirconium oxide, quartz powder, kaolin, bentonite, and titanium dioxide. The shape of these filler materials is not particularly limited and can include fibrous, needle-like, columnar, whisker-like, plate-like, layered, scaly, hollow spherical, porous, short fiber-like, powder-like, granular, and bead-like forms. It should be noted that these filler materials are different from boron nitride.

[0176] The foaming composition of the present invention may further contain a thermoplastic resin other than the aforementioned fluoropolymer. Examples of thermoplastic resins other than the aforementioned fluoropolymer include general-purpose resins such as polyethylene resin, polypropylene resin, vinyl chloride resin, and polystyrene resin; and engineering plastics such as nylon, polycarbonate, polyetheretherketone resin, polyphenylene sulfide resin, polyaryl ether ketone (PAEK), polyetherketone ketone (PEKK), polyetherketone (PEK), polyetheretherketone ketone (PEEKK), polyetheretherketone ketone (PEEKK), polyethersulfone (PES), liquid crystal polymer (LCP), polysulfone (PSF), amorphous polyarylate (PAR), polyether nitrile (PEN), thermoplastic polyimide (TPI), polyimide (PI), polyetherimide (PEI), and polyamide-imide (PAI).

[0177] The foaming composition of the present invention may further contain other components such as additives. Examples of other components include fillers such as glass fiber, glass powder, asbestos fiber, cellulose fiber, and carbon fiber, as well as reinforcing agents, stabilizers, lubricants, pigments, flame retardants, and other additives.

[0178] The foaming composition of the present invention can also be obtained, for example, by a manufacturing method (hereinafter referred to as "the manufacturing method of the composition") including the following mixing step, in which a fluoropolymer (A) and a compound (B) are mixed with boron nitride, filler, additives, etc., added as needed to obtain a mixture.

[0179] As a mixing method, for example, existing known methods can be used, but a mixing method in which the above-mentioned compound (B) is not easily aggregated is preferred.

[0180] Other methods of mixing described above include using a Henschel mixer, a belt mixer, a V-type agitator, a ball mill, etc. Additionally, methods involving melt mixing can also be used.

[0181] The method for manufacturing the foaming molding composition of the present invention may include a mixing step of kneading the mixture obtained by the above-described mixing step. Through this kneading, granules can be obtained. This kneading can be performed, for example, using a conventionally known melt mixer such as a single-screw extruder or a twin-screw extruder.

[0182] The method for manufacturing the above-described foaming molding composition may include a step of fluorinating a fluoropolymer. The fluorination treatment can be performed using the method described above. For example, the fluorination treatment can be carried out by contacting the granules obtained from the above-described compounding with the fluorinated compound.

[0183] The components that may be contained in the foaming composition of the present invention, as described above, include thermoplastic resins other than fluoropolymers; boron nitride; inorganic salts containing polyatomic anions; fillers; and other additives, which may be appropriately added in each step of the method for manufacturing the foaming composition according to their properties. Furthermore, fluoropolymers and boron nitride may be further added.

[0184] The foaming molding composition of the present invention is suitable for use as a foaming composition. Furthermore, the above-described foaming molding composition is suitable for use as a wire coating composition for forming a coating material for electrical wires.

[0185] The foaming composition of the present invention exhibits excellent foaming properties without using fluorinated surfactants. Existing fluorinated surfactants are generally low-molecular-weight fluorinated compounds. If a large amount of such low-molecular-weight fluorinated compounds are present, the molten resin during molding is plasticized, leading to increased sparking. Since the foaming composition of the present invention substantially does not contain such low-molecular-weight fluorinated compounds, the above-mentioned problems are not caused, and foamed molded articles with excellent surface conditions can be obtained.

[0186] There are no particular limitations on the aforementioned low-molecular-weight fluorine compounds; examples include perfluoroalkyl acids and perfluorosulfonic acids. Specifically, C8F... 17 COOH and its salts, C7F 15 COOH and its salts, C6F 13 COOH and its salts, C8F 17 SO3H and its salts, C6F 13 SO3H and its salts, C4F9SO3H and its salts, C8F 17 CH2CH2-SO3H and its salts, C6F 13 CH2CH2-SO3H and its salts, C8F 17 CH2CH2OH, C6F 13 CH2CH2OH, etc., and more specifically, {F(CF2)6CH2CH2SO3}2Ba.

[0187] The content of the above-mentioned low-molecular-weight fluorine compounds can be analyzed by the following methods.

[0188] The granules of the foaming molding composition were pulverized by freeze-drying, and the resulting powder was dispersed in methanol. Extraction was then performed by ultrasonic treatment at 60°C for 2 hours. The extract was quantified using liquid chromatography-mass spectrometry (LC-MS / MS), and the obtained value was taken as the content.

[0189] The method for manufacturing a foamed molded article of the present invention includes a step of foaming the above-mentioned foaming molding composition.

[0190] There are no particular limitations on the method for foaming the above-mentioned foaming molding composition. For example, existing known methods can be used, such as feeding the foaming molding composition of the present invention into a screw extruder designed for foaming operation using gas in the molten fluororesin (molten resin) using a continuous gas injection method; etc.

[0191] The aforementioned gas can be, for example, dichlorofluoromethane, nitrogen, carbon dioxide, or a mixture thereof. It can be introduced as a pressurized gas into the molten resin within the extruder, or it can be generated by mixing a chemical foaming agent into the molten resin. The gas is dissolved in the molten resin within the extruder.

[0192] Regarding the gas dissolved in the molten resin, the gas escapes from the molten material due to the sudden decrease in pressure during extrusion from the die. The extrudate is then cooled and solidified by methods such as introducing it into water.

[0193] The above-mentioned foamed molded body is obtained by foaming the above-mentioned foaming molding composition. Therefore, it has a low dielectric constant, exhibits stable capacitance, and is lightweight. As a coating material described later, it can achieve a shape with stable dimensions such as wire diameter and thickness.

[0194] The total volume of air bubbles in the foamed molded body can be appropriately adjusted according to the application, for example, by adjusting the amount of gas inserted in the extruder or by selecting the type of dissolved gas.

[0195] The aforementioned foamed molded body is obtained in the form of a molded body shaped according to its intended use when extruded from the aforementioned extruder. As for the aforementioned molding method, there is no particular limitation as long as it involves heating and melting molding, examples include extrusion foaming molding, injection foaming molding, and die foaming molding.

[0196] The shape of the aforementioned foamed material is not particularly limited, and it can be made into various shapes such as filaments, sheets, films, rods, and tubes, for example, as a coating material for foamed wires or other similar materials. The aforementioned foamed material can be used, for example, as a lightweight structural material such as an electrical insulation material, heat insulation material, sound insulation material, or buoyancy material, as well as a cushioning material such as a shock absorber. Furthermore, the aforementioned foamed material is particularly suitable for use as a coating material for foamed wires.

[0197] The resulting foamed molded body is preferably a foamed molded body containing a melt-cured body of the foaming molding composition of the present invention and bubbles, wherein the bubbles are uniformly distributed in the melt-cured body. The average bubble diameter is not limited, but is preferably 60 μm or less. Furthermore, the average bubble diameter is preferably 0.1 μm or more.

[0198] The foaming rate of the above-mentioned foamed molded article is not particularly limited, but is preferably 20% or more. The upper limit of the foaming rate is not particularly limited, for example, it is 80%.

[0199] One of the features of the foamed molded articles of the present invention is that the surface is smoother than that of conventional foamed molded articles containing fluororesin. Because of the smooth surface, it can be appropriately used for double-strand cables, etc.

[0200] In this invention, the surface of the foamed molded body can be evaluated by observing the degree of "snagging" (protrusions) transmitted to the hand when swept across it. Furthermore, as described later, the obtained image data is corrected using second-order surface correction with surface shape correction and the range of the wires is specified. A surface roughness of 500 × 2000 μm is then calculated, and a numerical evaluation is performed. The aforementioned surface roughness is preferably less than 10.0 μm and more preferably less than 7.0 μm. The lower limit of the surface roughness can be 0.001 μm or more.

[0201] The method for manufacturing the wire of the present invention includes a step of coating the above-described foaming molding composition onto a core wire to obtain the wire. By using the above-described foaming molding composition, a foamed wire having a coating material having fine and uniform air bubbles can be formed. The step of obtaining the wire is preferably a step of foaming the above-described foaming molding composition.

[0202] The wire obtained by the above-described wire manufacturing method consists of a coating material and a core wire, wherein the coating material is formed from the above-described foaming molding composition. A wire obtained by coating the core wire with the above-described foaming molding composition is also one aspect of the present invention.

[0203] The aforementioned coating material is obtained by coating the core wire with the aforementioned foaming molding composition, thus possessing fine and uniform bubbles. Furthermore, it has a low dielectric constant, exhibits stable capacitance, is lightweight, and can achieve a shape with stable dimensions such as wire diameter and thickness.

[0204] In addition, the aforementioned coating material has a smooth surface and exhibits the same physical properties as the aforementioned foamed molded body.

[0205] In addition to coating the core wire with the aforementioned foaming composition, the wire can be manufactured using the same methods as before, such as extrusion foaming. Preferred extrusion molding conditions can be appropriately selected based on the composition of the composition used and the size of the core wire.

[0206] As a method for coating the above-mentioned foaming molding composition onto the core wire, examples include: feeding the foaming molding composition of the present invention into a screw extruder designed for foaming operation using a gas that is soluble in molten fluororesin (molten resin), and using a continuous gas injection method; etc. The same gas used in the method for manufacturing the foamed molded body can be used as the gas described above.

[0207] The resulting coating material is preferably a coating material containing a melt-cured body of the foaming molding composition of the present invention and bubbles, wherein the bubbles are uniformly distributed in the melt-cured body.

[0208] The average bubble diameter is not limited, but is preferably 200 μm or less, more preferably 100 μm or less, even more preferably 50 μm or less, even more preferably 40 μm or less, particularly preferably 30 μm or less, and especially preferably 20 μm or less. Furthermore, the average bubble diameter is preferably 0.1 μm or more, more preferably 0.5 μm or more, and even more preferably 1 μm or more.

[0209] The structure of this coating material is obtained by combining the fluoropolymer (A) and a specific compound (B) in the foaming molding composition of the present invention.

[0210] The average bubble diameter mentioned above was obtained by the following method: an image of the cross-section of the coated material was obtained using a scanning electron microscope (SEM), and the diameter of each bubble was calculated and averaged through image processing.

[0211] The foaming rate of the aforementioned coating material is preferably 20% or more. More preferably, it is 30% or more, further preferably 40% or more, and even more preferably 43% or more. There is no particular upper limit, for example, it is 90%. The upper limit of the foaming rate can also be 80%.

[0212] The foaming rate described above is calculated as ((specific gravity of fluororesin - specific gravity of foam) / specific gravity of fluororesin) × 100. This foaming rate can be appropriately adjusted according to the application, for example, by adjusting the gas insertion rate in the extruder or by selecting the type of dissolved gas.

[0213] The number of sparks per 3500m of the aforementioned coating material is preferably less than 5. More preferably less than 3, and even more preferably less than 1.

[0214] The above spark count was obtained using a Beta LaserMike HFS1220 spark meter at 1500V.

[0215] For the core wire, materials such as copper, aluminum, or carbon conductors can be used. Alternatively, it can be a single material or the surface can be plated with silver or tin.

[0216] The diameter of the core wire is preferably 0.02 mm to 3 mm. More preferably, the diameter is 0.04 mm or more, even more preferably 0.05 mm or more, and particularly preferably 0.1 mm or more. More preferably, the diameter is 2 mm or less. Furthermore, the core wire can be a single wire or a stranded wire formed by twisting multiple core wires together.

[0217] There are no particular limitations on the shape of the core wire; examples include flat shapes and flat wires.

[0218] Preferably, the thickness of the coating material for the aforementioned wire is 0.01 mm to 3.0 mm. The thickness of the coating material is also preferably 2.0 mm or less.

[0219] Specific examples of core wires include AWG (American Wire Gauge)-46 (solid copper wire with a diameter of 40 micrometers), AWG-42 (solid copper wire with a diameter of 64 micrometers), AWG-36 (a wire with a total diameter of 153 micrometers, consisting of 7 strands of solid copper wire with a diameter of 127 micrometers and 7 strands of copper wire with a diameter of 51 micrometers), AWG-30 (a wire with a total diameter of 306 micrometers, consisting of 7 strands of solid copper wire with a diameter of 254 micrometers and 7 strands of copper wire with a diameter of 102 micrometers), AWG-27 ​​(solid copper wire with a diameter of 361 micrometers), AWG-26 (solid copper wire with a diameter of 404 micrometers), AWG-24 (solid copper wire with a diameter of 510 micrometers), and AWG-22 (solid copper wire with a diameter of 635 micrometers).

[0220] The aforementioned foamed wires consist of a core wire and a coating material for the core wire. These foamed wires are suitable for use as cables connecting computers and their peripherals, high-speed communication cables for high-capacity video or audio, cables connecting servers in data centers, such as LAN cables, USB cables, Lightning cables, Thunderbolt cables, CATV cables, HDMI (registered trademark) cables, QSFP cables, aerospace cables, underground power transmission cables, submarine power cables, high-voltage cables, superconducting cables, packaged wires, automotive cables, wire harnesses and electrical equipment, robotic and computer-aided design (FA) cables, OA equipment cables, information equipment cables (fiber optic cables, audio cables, etc.), internal wiring for communication base stations, high-current internal wiring (inverters, power regulators, battery systems, etc.), internal wiring for electronic equipment, small electronic equipment and mobile wiring, moving part wiring, internal wiring for electrical equipment, internal wiring for measuring equipment, power cables (for construction, wind / solar power generation, etc.), control and measurement wiring cables, and motor cables, etc.

[0221] The aforementioned wire can be a two-layer structure (surface-foam) formed by inserting a non-foamed layer between the core wire and the covering material, a two-layer structure (foam-surface) formed by covering the outer layer with a non-foamed layer, or a three-layer structure (surface-foam-surface) formed by further covering the outer layer of the surface-foam with a non-foamed layer.

[0222] The non-foamed layer of the aforementioned wire is not particularly limited and can be a resin layer composed of TFE / HFP copolymer, TFE / PAVE copolymer, TFE / ethylene copolymer, vinylidene fluoride polymer, polyethylene [PE] and other polyolefin resins, polyvinyl chloride [PVC] and other resins.

[0223] The foaming composition of the present invention substantially does not contain fluorine-based low molecular weight compounds; therefore, the foamed molded body and the wire described above also substantially do not contain fluorine-based low molecular weight compounds.

[0224] The content of fluorine-based low-molecular-weight compounds in the above-mentioned foamed molded articles and wires can be analyzed in the same way as in the case of the above-mentioned foamed molding compositions.

[0225] The present invention also relates to the following types of foamed wires.

[0226] (1) A foamed wire having a core wire and a fluoropolymer layer or fluoropolymer composition layer covering the core wire, wherein the fluoropolymer layer or fluoropolymer composition layer has air bubbles, wherein the average aspect ratio of the air bubbles is 1.9 or less when viewed in a cross section parallel to the length direction.

[0227] (2) A foamed wire having a core wire and a fluoropolymer layer or fluoropolymer composition layer covering the core wire, wherein the fluoropolymer layer or fluoropolymer composition layer has air bubbles, wherein the foamed wire is characterized in that, in a cross-sectional view parallel to the length direction, the proportion of air bubbles with an aspect ratio of 3 or more is 13% or less relative to the total amount of air bubbles measured in a cross-sectional view parallel to the length direction.

[0228] (3) A foamed wire having a core wire and a fluoropolymer layer or fluoropolymer composition layer covering the core wire, wherein the fluoropolymer layer or fluoropolymer composition layer has air bubbles, wherein the standard deviation of the aspect ratio of the air bubbles is 1.3 or less when viewed in a cross section parallel to the length direction.

[0229] (4) A foamed wire having a core wire and a fluoropolymer layer or fluoropolymer composition layer covering the core wire, wherein the fluoropolymer layer or fluoropolymer composition layer has air bubbles.

[0230] The foamed wire is characterized by a foaming rate of over 35% and a surface roughness of less than 9.0 μm.

[0231] The bubbles contained in the fluoropolymer layer or fluoropolymer composition layer satisfy these physical properties, indicating that it has fine and uniform bubbles, and can be said to have a low dielectric constant and exhibit stable capacitance.

[0232] These fluoropolymer layers and fluoropolymer composition layers can be formed, for example, by the foaming molding composition of the present invention.

[0233] The average aspect ratio of the aforementioned bubbles is 1.9 or less. This average aspect ratio can be determined as follows: An image of a cross-section parallel to the length direction of the coating material is obtained using a scanning electron microscope (SEM). The ratio of the major axis to the minor axis (major axis / minor axis) of each bubble is calculated from the major and minor axes obtained through image processing. The aspect ratios obtained are then averaged to determine the aspect ratio. The average aspect ratio is preferably 1.8 or less, more preferably 1.6 or less. Furthermore, it is preferably 1.0 or more.

[0234] The proportion of bubbles with an aspect ratio of 3 or higher is less than 13% of the total number of bubbles measured in a cross-section observed parallel to the length direction. This proportion is calculated as follows: Using a scanning electron microscope (SEM), an image of a cross-section parallel to the length direction of the coated material is obtained. The ratio of the major axis to the minor axis (major axis / minor axis) of each bubble is calculated from the major and minor axes obtained through image processing. The proportion of bubbles with an aspect ratio of 3 or higher is then calculated from this.

[0235] The proportion of bubbles with an aspect ratio of 3 or more is preferably 6% or less, more preferably 3% or less. Furthermore, it is preferably 0.01% or more.

[0236] The standard deviation of the aspect ratio of the aforementioned bubbles is 1.3 or less. This standard deviation is calculated as follows: An image of a cross-section parallel to the length direction of the coating material is obtained using a scanning electron microscope (SEM). The ratio of the major axis to the minor axis (major axis / minor axis) of each bubble is calculated from the major and minor axes obtained through image processing. The standard deviation of the aspect ratio obtained from this is then calculated. Preferably, the standard deviation of the aspect ratio is 1.1 or less, more preferably 0.8 or less, and even more preferably 0.6 or less. Furthermore, it is preferably 0.01 or more.

[0237] The foaming rate is 35% or higher. The foaming rate is calculated as ((specific gravity of fluororesin - specific gravity of fluororesin layer or fluororesin composition layer) / specific gravity of fluororesin) × 100.

[0238] The foaming rate is more preferably 40% or more, and even more preferably 43% or more.

[0239] The surface roughness mentioned above is below 9.0 μm. The surface roughness mentioned above is calculated as follows: the surface of the wire was measured using a Keyence laser microscope. After specifying the range of the wire in the obtained image data through second-order surface correction with surface shape correction and applying the correction, the surface roughness of 500 × 200 μm was calculated.

[0240] The surface roughness is more preferably 8.0 μm or less, and even more preferably 7.0 μm or less.

[0241] Preferably, the average bubble diameter of the foamed wire observed in a cross-section perpendicular to its length is 40 μm or less. This average bubble diameter is calculated by obtaining an image of the cross-section of the coating material using a scanning electron microscope (SEM), calculating the diameter of each bubble through image processing, and then averaging the values. More preferably, the average bubble diameter is 30 μm or less; even more preferably, 25 μm or less; and particularly preferably, 20 μm or less. It is also more preferably 0.1 μm or more.

[0242] In the aforementioned foamed wire, the coating thickness of the fluororesin layer or fluororesin composition layer is preferably 0.4 mm or less, more preferably 0.3 mm or less, and even more preferably 0.25 mm or less. The coating thickness is a value calculated as (outer diameter of the wire coating - core wire diameter) / 2.

[0243] In the aforementioned foamed wire, the core wire diameter is preferably 0.5 mm or less, more preferably 0.4 mm or less, and even more preferably 0.3 mm or less.

[0244] The manufacturing method of the aforementioned foamed wire is not particularly limited, but it is preferable to manufacture it using the manufacturing method of the foamed wire using the foaming molding composition of the present invention. That is, by using the foaming molding composition of the present invention, a foamed wire with the above-mentioned properties can be obtained, thereby obtaining various excellent properties.

[0245] The manufacturing method of the foamed wire of the present invention can be carried out through the above-described steps.

[0246] Example

[0247] The present invention will now be described in detail based on specific embodiments.

[0248] Preparation of Granule A in Manufacturing Example 1

[0249] Granules A were obtained using the same method as described in Example 1 of Japanese Patent Application Publication No. 2017-128119. The resulting granules had the following composition: TFE / HFP / PPVE copolymer, TFE / HFP / PPVE = 87.8 / 11.2 / 1.0 (mass ratio), melting point: 255°C, melt flow rate (MFR): 37 g / 10 min, and the total number of unstable terminal groups and -CF2H terminal groups relative to 1 × 10⁻⁶. 6 The number of carbon atoms is 0.

[0250] Preparation of Granule B in Example 2

[0251] Granules (B) were prepared using the same method as in Manufacturing Example 1, except that the amount of ammonium persulfate used to adjust the molecular weight was changed. The resulting granules were a TFE / HFP / PPVE copolymer, with TFE / HFP / PPVE = 87.8 / 11.2 / 1.0 (mass ratio), melting point: 255°C, melt flow rate (MFR): 30 g / 10 min, and the total number of unstable terminal groups and -CF2H terminal groups per 1 × 10 6 There are 10 carbon atoms in each carbon atom.

[0252] Preparation of Granule C in Example 3

[0253] The pellets obtained using the same method as described in Synthesis Example 1 of WO2005-052015 were fluorinated to obtain pellet C. The resulting pellets were composed of a TFE / PPVE copolymer, with TFE / PPVE = 94.9 / 5.1 (mass ratio), melting point: 255°C, melt flow rate (MFR): 63 g / 10 min, and the total number of unstable terminal groups and -CF2H terminal groups relative to 1 × 10 6 The number of carbon atoms is 0.

[0254] In the molding of foamed wires, for the granules (composition) adjusted by melt mixing to achieve the specified addition amount, the extruder temperature is set as shown in Table 1. Φ0.30mm copper wire is used as the core wire. The extrusion temperature, nitrogen inlet flow rate (pressure), extrusion speed, and traction speed are adjusted to achieve an outer diameter of 0.80mm after coating and a capacitance of 0.86pF / m (equivalent to a foaming rate of 43%). The wire extrusion conditions are shown in Table 2.

[0255] After one hour of continuous operation, for a stable 3500m length, wire diameter fluctuations, capacitance shifts, and spark out were observed. Furthermore, for the obtained foamed wire, the foaming rate and average foam diameter were determined using the following methods, surface condition was observed, and surface roughness was measured.

[0256] The obtained wires were evaluated for various characteristics, and the results are shown in Tables 3 and 4.

[0257] It should be noted that the additives in Tables 3 and 4 are as follows.

[0258] NA11: Sodium 2,2'-methylenebis(4,6-di-tert-butylphenyl)phosphate

[0259] C1 280~340℃ C2 320~380℃ C3 340~400℃ C4 340~400℃ C5 340~400℃ H1 340~400℃ H2 330~400℃ H3 300~400℃

[0260] Table 2

[0261]

[0262] The various characteristics described in this specification were measured using the following methods.

[0263] (Determination of the number of unstable terminal groups)

[0264] The granules were rolled using a hydraulic press to produce a membrane with a thickness of approximately 0.3 mm. The membrane was then analyzed using an FT-IR Spectrometer 1760X (manufactured by Perkin-Elmer).

[0265] Obtain the differential spectrum with the standard sample (the sample that has been fully fluorinated until no substantial difference is found in the spectrum), read the absorbance of each peak, and calculate the absorbance per 1×10⁻⁶ peaks using the following formula. 6 The number of unstable terminal groups with a carbon atom count.

[0266] Each 1×10 6 The number of unstable terminal groups with a carbon atom count = (I×K) / t

[0267] (I: absorbance, K: correction factor, t: film thickness (unit: mm))

[0268] The correction coefficients (K) for each unstable terminal group are as follows.

[0269] -COF(1884cm -1 )···405

[0270] -COOH(1813cm -1 1775cm -1 )···455

[0271] -COOCH3(1795cm -1 )···355

[0272] -CONH2(3438cm -1 )···480

[0273] -CH2OH(3648cm -1 )···2325

[0274] (Determination of the number of -CF2H terminal groups)

[0275] The measurement was performed using an AC300 nuclear magnetic resonance apparatus (manufactured by Bruker-Biospin), with the measurement temperature set to (melting point of the fluoropolymer + 20) °C. 19 F-NMR determination, obtained by integrating the peaks originating from the presence of the -CF2H group with the integrals of other peaks.

[0276] (Melting point)

[0277] Regarding the melting point of fluoropolymers, the temperature corresponding to the peak measured using an RDC220 (manufactured by SEIKO Electronics) at a heating rate of 10°C / minute will be taken as the melting point.

[0278] (MFR)

[0279] The MFR of fluoropolymers is the value measured according to ASTM D-1238 using a KAYENESS Melt Flow Index Tester 4000 series (manufactured by Yasuda Seiki Co., Ltd.) with a die head of 2.1 mm in diameter and 8 mm in length, at 372°C and a 5 kg load.

[0280] (outer diameter)

[0281] The outer diameter of the wire was measured using a Laser Micro Dieuter LDM-303H-XY (manufactured by Takikawa Engineering).

[0282] (Capacitance)

[0283] Capacitance was measured using a CAPAC300 19C (manufactured by Zumbach).

[0284] (Number of sparks)

[0285] The number of sparks per 3500m was measured using a Beta LaserMike HFS1220 spark meter at a voltage of 1500V.

[0286] (Foaming rate)

[0287] The value is calculated as ((specific gravity of fluororesin - specific gravity of foam) / specific gravity of fluororesin) × 100.

[0288] (Average bubble diameter)

[0289] Obtain an SEM image of the wire cross-section, calculate the diameter of each bubble through image processing, and average them to obtain the average bubble diameter.

[0290] (Surface condition)

[0291] Run your hand across the surface of the covered wire and evaluate the degree of grip (protrusion) transmitted to your hand at this time.

[0292] It's great that it didn't get caught.

[0293] Good, but slightly hanging on.

[0294] The problem is severe.

[0295] (Surface roughness)

[0296] The surface roughness of the wire was measured using a Keyence laser microscope. The range of the wire was specified by a second-order surface correction with surface shape correction, and the surface roughness of 500×2000μm was calculated.

[0297] Example 1

[0298] Adding 0.5 parts by mass of sodium 2,2'-methylenebis(4,6-di-tert-butylphenyl) phosphate (ADKSTAB NA-11, a nucleating agent manufactured by ADEKA Co., Ltd.; melting point ≥400℃) to granules (A), and then extruding the resulting granules at an extrusion speed of 15 rpm, a nitrogen inlet flow rate of 18 cc / min, and a traction speed of 102 m / min to form foamed wires, yielded foamed wires with a target outer diameter of 0.80 mm and a capacitance of 86.6 pF / m. The standard deviation of wire diameter non-uniformity was 0.003, and the standard deviation of capacitance non-uniformity was 0.3, which are good. The spark count was also very good at 2. Analysis of the obtained foamed wires showed a foaming rate of 43%, an average bubble diameter of 17 μm, which are good, an excellent surface feel, and a very good surface roughness of 6.6 μm. Furthermore, no fluorine-based low-molecular-weight compounds were detected in the granules used or the produced foamed wires.

[0299] A cross-sectional photograph of the wire obtained in Example 1 is shown below. Figure 1 .

[0300] In addition, photos of the surface condition are shown. Figure 12 .

[0301] Example 2

[0302] Adding 1.0 parts by weight of sodium 2,2'-methylenebis(4,6-di-tert-butylphenyl) phosphate (ADKSTAB NA-11 crystallizing nucleating agent manufactured by ADEKA Corporation) to granules (A), and then extruding the resulting granules at an extrusion speed of 15 rpm, a nitrogen inlet flow rate of 16 cc / min, and a traction speed of 100 m / min to form foamed wires, a foamed wire with a target outer diameter of 0.80 mm and a capacitance of 86.1 pF / m was obtained. The standard deviation of wire diameter non-uniformity was 0.003, and the standard deviation of capacitance non-uniformity was 0.2, which are good. The spark count was also very good at 3. Analysis of the obtained foamed wire showed a foaming rate of 43%, an average bubble diameter of 14 μm, which are good, an excellent surface feel, and a very good surface roughness of 6.9 μm.

[0303] A cross-sectional photograph of the wire obtained in Example 2 is shown below. Figure 2 .

[0304] In addition, photos of the surface condition are shown. Figure 13 .

[0305] Example 3

[0306] 0.5 parts by mass of sodium 2,2'-methylenebis(4,6-di-tert-butylphenyl) phosphate (ADKSTAB NA-11, a crystallizing nucleating agent manufactured by ADEKA Corporation) and 1.0 parts by mass of PFA were added to granules (A). The resulting granules were extruded at a speed of 15 rpm, a nitrogen inlet flow rate of 18 cc / min, and a traction speed of 104 m / min to form foamed wires. Foamed wires with a target outer diameter of 0.80 mm and a capacitance of 86.5 pF / m were obtained. The standard deviation of wire diameter non-uniformity was 0.003, and the standard deviation of capacitance non-uniformity was 0.3, which are good. The spark count was also very good at 2. Analysis of the obtained foamed wires showed that the foaming rate was 43%, the average bubble diameter was 18 μm, which is good, the surface feel was extremely good, and the surface roughness was also very good at 6.8 μm.

[0307] A cross-sectional photograph of the wire obtained in Example 3 is shown below. Figure 3 .

[0308] In addition, photos of the surface condition are shown. Figure 14 .

[0309] Example 4

[0310] Adding 0.5 parts by mass of sodium 2,2'-methylenebis(4,6-di-tert-butylphenyl) phosphate (ADKSTAB NA-11, a nucleating agent manufactured by ADEKA Corporation; melting point ≥400℃) to granules (C), and then extruding the resulting granules at an extrusion speed of 15 rpm, a nitrogen inlet flow rate of 18 cc / min, and a traction speed of 102 m / min to form foamed wires, yielded foamed wires with a target outer diameter of 0.80 mm and a capacitance of 86.3 pF / m. The standard deviation of wire diameter non-uniformity was 0.004, and the standard deviation of capacitance non-uniformity was 0.3, which are good. The spark count was also very good at 1. Analysis of the obtained foamed wires showed a foaming rate of 43%, an average bubble diameter of 19 μm, which are good, an excellent surface feel, and a very good surface roughness of 6.8 μm.

[0311] A cross-sectional photograph of the wire obtained in Example 4 is shown below. Figure 4 .

[0312] In addition, photos of the surface condition are shown. Figure 15 .

[0313] Comparative Example 1

[0314] No substances were added to the granules (A). The resulting granules were extruded at a speed of 15 rpm, a nitrogen inlet flow rate of 21 cc / min, and a traction speed of 70 m / min to form foamed wires. Foaming was barely observed, and the OD (expansion distance) and capacitance were extremely uneven. The desired foamed wire was not obtained.

[0315] Comparative Example 2

[0316] Adding 1.0 part by mass of boron nitride to granules (A), the resulting granules were extruded at a speed of 15 rpm, a nitrogen inlet flow rate of 20 cc / min, and a traction speed of 106 m / min to form foamed wires. This yielded foamed wires with a target outer diameter of 0.80 mm and a capacitance of 86.2 pF / m. The standard deviation of wire diameter non-uniformity was 0.004, the standard deviation of capacitance non-uniformity was as large as 1.9, and the spark count was also very poor, exceeding 100. Analysis of the obtained foamed wires revealed a foaming rate of 43%, an average bubble diameter as large as 36 μm, poor surface condition, and a surface roughness of 12.4 μm.

[0317] A cross-sectional photograph of the wire obtained in Comparative Example 2 is shown below. Figure 5 .

[0318] In addition, photos of the surface condition are shown. Figure 16 .

[0319] Comparative Example 3

[0320] Adding 0.0281 parts by mass of barium fluorooctane sulfonate, 0.011 parts by mass of calcium tetraborate, and 0.4 parts by mass of boron nitride to granules (B), the resulting granules were extruded at a speed of 15 rpm, a nitrogen inlet flow rate of 13 cc / min, and a traction speed of 100 m / min to form foamed wires. Foamed wires with a target outer diameter of 0.80 mm and a capacitance of 86.4 pF / m were obtained. The standard deviation of wire diameter non-uniformity was 0.005, while the standard deviation of capacitance non-uniformity was slightly larger at 0.6, and the number of sparks was as high as 12. Analysis of the obtained foamed wires showed a foaming rate of 43%, an average bubble diameter of 14 μm (good), a good surface feel, and a poor surface roughness of 10.0 μm. Furthermore, 11 ppm and 16 ppm of {F(CF2)6CH2CH2SO3}2Ba were detected in the granules and the foamed wires, respectively.

[0321] A cross-sectional photograph of the wire obtained in Comparative Example 3 is shown below. Figure 6 .

[0322] In addition, photos of the surface condition are shown. Figure 17 .

[0323] Comparative Example 4

[0324] Adding 0.1 parts by mass of barium fluorooctane sulfonate to granules (A), the resulting granules were extruded at a speed of 15 rpm, a nitrogen inlet flow rate of 16 cc / min, and a traction speed of 90 m / min to form foamed wires. This yielded foamed wires with a target outer diameter of 0.80 mm and a capacitance of 86.5 pF / m. The standard deviation of wire diameter non-uniformity was 0.007, while the standard deviation of capacitance non-uniformity was slightly larger at 0.7, with as many as 9 sparks. Analysis of the obtained foamed wires showed a foaming rate of 43%, an average bubble diameter of 17 μm (good), a good surface feel, and a poor surface roughness of 10.9 μm.

[0325] A cross-sectional photograph of the wire obtained in Comparative Example 4 is shown below. Figure 7 .

[0326] In addition, photos of the surface condition are shown. Figure 18 .

[0327] Comparative Example 5

[0328] Adding 0.08 parts by mass of barium fluorooctane sulfonate and 0.01 parts by mass of calcium tetraborate to granules (A), the resulting granules were extruded at a speed of 15 rpm, a nitrogen inlet flow rate of 16 cc / min, and a traction speed of 90 m / min to form foamed wires. This yielded foamed wires with a target outer diameter of 0.80 mm and a capacitance of 86.5 pF / m. The standard deviation of wire diameter non-uniformity was 0.005, and the standard deviation of capacitance non-uniformity was good at 0.3, but the number of sparks was as high as 8. Analysis of the obtained foamed wires showed a foaming rate of 43%, an average bubble diameter of 17 μm (good), a good surface feel, and a poor surface roughness of 10.4 μm.

[0329] A cross-sectional photograph of the wire obtained in Comparative Example 5 is shown below. Figure 8 .

[0330] In addition, photos of the surface condition are shown. Figure 19 .

[0331] Comparative Example 6

[0332] Adding 0.01 parts by mass of sodium fluorobutane sulfonate and 0.4 parts by mass of boron nitride to granules (A), the resulting granules were extruded at a speed of 15 rpm, a nitrogen inlet flow rate of 20 cc / min, and a traction speed of 90 m / min to form foamed wires. This yielded foamed wires with a target outer diameter of 0.80 mm and a capacitance of 86.1 pF / m. The standard deviation of wire diameter non-uniformity was 0.004, and the standard deviation of capacitance non-uniformity was good at 0.4, but the number of sparks was as high as 15. Analysis of the obtained foamed wires showed a foaming rate of 43%, a large average bubble diameter of 30 μm, poor surface feel, and a poor surface roughness of 12.3 μm.

[0333] A cross-sectional photograph of the wire obtained in Comparative Example 6 is shown below. Figure 9 .

[0334] In addition, photos of the surface condition are shown. Figure 20 .

[0335] Comparative Example 7

[0336] Adding 0.1 parts by mass of barium fluorobutane sulfonate to granules (A), the resulting granules were extruded at a speed of 15 rpm, a nitrogen inlet flow rate of 20 cc / min, and a traction speed of 90 m / min to form foamed wires. This yielded foamed wires with a target outer diameter of 0.80 mm and a capacitance of 86.1 pF / m. The standard deviation of wire diameter non-uniformity was 0.004, and the standard deviation of capacitance non-uniformity was good at 0.3, but the number of sparks was as high as 8. Analysis of the obtained foamed wires showed a foaming rate of 43%, an average bubble diameter of 17 μm (good), a good surface feel, and a poor surface roughness of 10.0 μm.

[0337] A cross-sectional photograph of the wire obtained in Comparative Example 7 is shown below. Figure 10 .

[0338] In addition, photos of the surface condition are shown. Figure 21 .

[0339] Example 5

[0340] Adding 1.0 parts by mass of bisphenol phosphate diester (Ba salt, melting point ≥400℃) to granules (A), the resulting granules were extruded at a speed of 15 rpm, a nitrogen inlet flow rate of 14 cc / min, and a traction speed of 105 m / min to form foamed wires. This yielded foamed wires with a target outer diameter of 0.80 mm and a capacitance of 86.2 pF / m. The standard deviation of wire diameter non-uniformity was 0.003, and the standard deviation of capacitance non-uniformity was 0.3, both considered good. The spark count was also very good at 2. Analysis of the obtained foamed wires showed a foaming rate of 43%, an average bubble diameter of 18 μm (good), an excellent surface feel, and a very good surface roughness of 6.7 μm.

[0341] A cross-sectional photograph of the wire obtained in Example 5 is shown below. Figure 23 .

[0342] In addition, photos of the surface condition are shown. Figure 24 .

[0343] Example 6

[0344] Adding 1.0 parts by weight of N,N'-dicyclohexyl-2,6-naphthalenedicarboxamide (NJSTARNU-100, a nucleating agent manufactured by Shin Nippon Rikka Co., Ltd.; melting point ≥400℃) and 1.0 parts by weight of PFA to granules (A), the resulting granules were extruded at a speed of 15 rpm, a nitrogen inlet flow rate of 16 cc / min, and a traction speed of 96 m / min to form foamed wires. Foamed wires with a target outer diameter of 0.80 mm and a capacitance of 86.5 pF / m were obtained. The standard deviation of wire diameter non-uniformity was 0.004, the standard deviation of capacitance non-uniformity was 0.3 (good), and the spark count was also very good at 6. Analysis of the obtained foamed wires showed a foaming rate of 43%, an average bubble diameter of 22 μm (good), an extremely good surface feel, and a very good surface roughness of 8.0 μm.

[0345] A cross-sectional photograph of the wire obtained in Example 6 is shown below. Figure 25 .

[0346] In addition, photos of the surface condition are shown. Figure 26 .

[0347] Comparative Example 8

[0348] Adding 0.1 parts by mass of sodium phenylphosphonate to granules (A), the resulting granules were extruded at a speed of 15 rpm, a nitrogen inlet flow rate of 18 cc / min, and a traction speed of 100 m / min to form foamed wires. This yielded foamed wires with a target outer diameter of 0.80 mm and a capacitance of 86.3 pF / m. The standard deviation of wire diameter non-uniformity was 0.005, the standard deviation of capacitance non-uniformity was large (0.9), and the spark count was also very poor (over 100). Analysis of the obtained foamed wires showed a foaming rate of 43%, a large average bubble diameter of 45 μm, poor surface condition, and a poor surface roughness of 13.5 μm.

[0349] A cross-sectional photograph of the wire obtained in Comparative Example 8 is shown below. Figure 11 .

[0350] In addition, photos of the surface condition are shown. Figure 22 .

[0351] Comparative Example 9

[0352] 1.0 part by weight of 2,6-naphthalenedicarboxylic acid was added to the granules (A). The resulting granules were extruded at a speed of 15 rpm and a nitrogen inlet flow rate of 18 cc / min to form foamed wires. However, the additives decomposed violently and the target foamed wires were not obtained.

[0353] Comparative Example 10

[0354] 1.0 part by weight of 1,3:2,4-bis-O-(4-methylbenzyl)-D-sorbitol (GEL ALL MD, a crystallizing nucleating agent manufactured by Shin Nippon Rikka Co., Ltd.) was added to the granules (A). The resulting granules were extruded at a speed of 15 rpm and a nitrogen inlet flow rate of 18 cc / min to form foamed wires. However, the additives decomposed violently, and the target foamed wires were not obtained.

[0355] Comparative Example 11

[0356] 1.0 part by weight of N,N'-bis(octadecyl)isophthalamide was added to the granules (A), and the resulting granules were extruded at a speed of 15 rpm and a nitrogen inlet flow rate of 18 cc / min to form foamed wires. However, the additives decomposed violently, and the target foamed wires were not obtained.

[0357] Table 3

[0358]

[0359]

[0360] Industrial applicability

[0361] The foaming composition of the present invention is particularly suitable as a coating material for forming foamed wires.

Claims

1. A composition for foam molding, characterized in that, It contains a fluoropolymer (A) and a compound (B) that functions as a foaming nucleating agent with a thermal decomposition temperature of 300°C or higher and a solubility parameter SP value of 8 to 15.

2. The composition for foaming molding as described in claim 1, wherein, Compound (B) is a compound containing at least one of the following groups: an aromatic ring, a phosphate group, and an amide group.

3. The composition for foaming molding as described in claim 2, wherein, Compound (B) is a compound containing one or more aromatic rings of C6-14 or a salt thereof.

4. The composition for foaming molding as described in claim 2, wherein, Compound (B) is at least one compound selected from the group consisting of phosphate esters and their salts, phosphate ester complexes, and compounds having two or more amide groups.

5. The composition for foaming molding as described in claim 4, wherein, The salts of compound (B) are alkali metals or alkaline earth metals.

6. The composition for foam molding as described in any one of claims 2 to 5, wherein, Compound (B) is at least one of the compounds shown in formulas (1), (2), (3) and (4) below. 【Chemistry 1】 【Chemistry 2】 【Transformation 3】 【Chemistry 4】 In the formula, R1, R2, R3, R4, R 21 R 22 R 23 R 24 R 31 R 32 R 33 R 34 R 41 R 42 Ar represents hydrogen atoms, alkyl or cycloalkyl groups having 1 to 8 carbon atoms, or aryl, alkylaryl, or aralkyl groups having 6 to 12 carbon atoms. 41 R5 and R6 represent hydrogen atoms or methyl groups, n represents an integer of 1 or 2, m represents an integer from 0 to 2, and X represents a metal with a valence of m+n.

7. The composition for foaming molding as described in claim 6, wherein, R1, R2, R in equations (1), (2), and (3) 21 R 22 R 31 and R 33 It is an alkyl group having 1 to 8 carbon atoms.

8. The composition for foaming molding as described in claim 6, wherein, In formulas (1), (2), and (3), X is at least one of sodium, potassium, rubidium, calcium, and barium.

9. The composition for foaming molding as described in claim 7, wherein, In formulas (1), (2), and (3), X is at least one of sodium, potassium, rubidium, calcium, and barium.

10. The composition for foaming molding as claimed in claim 6, wherein, Compound (B) is an aromatic cyclic phosphate salt as shown in formula (1) above.

11. The composition for foaming molding as claimed in claim 10, wherein, Compound (B) is sodium 2,2'-methylenebis(4,6-di-tert-butylphenyl) phosphate.

12. The composition for foaming molding according to any one of claims 1 to 5, wherein, Fluororheological resin (A) is a fluoropolymer that can be melt-processed.

13. The composition for foaming molding according to any one of claims 1 to 5, wherein, Fluoropolymer (A) is at least one selected from the group consisting of tetrafluoroethylene / hexafluoropropylene copolymer, tetrafluoroethylene / perfluoro(alkyl vinyl ether) copolymer, and tetrafluoroethylene / ethylene copolymer.

14. The composition for foaming molding according to any one of claims 1 to 5, wherein, Fluoropolymer (A) is a fluorinated fluoropolymer.

15. The composition for foaming molding according to any one of claims 1 to 5, wherein it substantially does not contain fluorine-based low molecular weight compounds.

16. A foamed molded body, characterized in that, It is obtained from the foaming molding composition according to any one of claims 1 to 15.

17. The foamed molded article as described in claim 16 does not substantially contain fluorine-based low molecular weight compounds.

18. A foamed wire, characterized in that, It comprises a core wire and a coating material obtained by foaming molding composition according to any one of claims 1 to 15 covering the core wire.

19. The foamed wire as described in claim 18, in essence, does not contain fluorine-based low-molecular-weight compounds.

20. A method for manufacturing a foamed molded article, characterized in that, It includes the process of foaming the composition for foaming molding according to any one of claims 1 to 15.

21. A method for manufacturing an electrical wire, characterized in that, It includes the process of coating a core wire with the foaming composition according to any one of claims 1 to 15 to obtain an electric wire.

Citation Information

Patent Citations

  • Expandable fluoropolymer composition

    JP1998045931A

  • Composition for wallpaper

    JP1999130892A

  • Composition, and method for producing foam molded material and electric wire

    JP2014224229A

  • Pellet of fluorine resin, electric wire and method for producing the same

    JP2017128119A

  • Foam nucleation system for fluoropolymers

    US4764538A